2020
DOI: 10.47176/mjiri.34.38
|View full text |Cite
|
Sign up to set email alerts
|

Stillbirth in Iran and associated factors (2014-2016): A population-based study

Abstract: Before the implementation of Iranian Maternal and Neonatal Network (IMaN), our estimation of national and provincial stillbirth rate was limited to rural areas and a nonrandom urban subpopulation, without any details on maternal or neonatal conditions. →What this article adds:We estimated the average stillbirth rate of 7.42 per 1000 total births during 2014-2016 in Iran. The highest stillbirth rates occurred in the southeast and northwest of the country. Iran has achieved stillbirth target of Every Newborn Act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Chen et al They also estimated the Cronbach's α of the scale and subscales of the CIAS questionnaire in the initial study, between 0.79 and 0.93. [15] Cronbach's α value of these constructs was calculated as 0.94 in another study conducted by Mak et al [16]. Therefore, the results of the studies con rm the high reliability of this questionnaire.…”
Section: Discussionmentioning
confidence: 66%
“…Chen et al They also estimated the Cronbach's α of the scale and subscales of the CIAS questionnaire in the initial study, between 0.79 and 0.93. [15] Cronbach's α value of these constructs was calculated as 0.94 in another study conducted by Mak et al [16]. Therefore, the results of the studies con rm the high reliability of this questionnaire.…”
Section: Discussionmentioning
confidence: 66%
“…A research study showed that 70% of DM patients without peripheral neuropathy had insufficient health literacy levels (Mohammadi et al, 2015 ). Among the DPN patients in this study, the number of HL deficiencies was even higher, at 74.1%.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Greater than 97% of deliveries in Iran occur in hospitals, making the IMaN database a reliable sample of pregnancy and its complications throughout the country and an important source of epidemiological information for SARS-CoV-2 information in newborns. 11,12 Study patients included liveborn neonates 28 days of age having suspected as well as confirmed SARS-CoV-2 infection that were admitted to the hospital following delivery. Inclusion criteria for suspected cases included having a clinical presentation consistent with neonatal COVID-19 or those neonates having a positive history of contact with SARS-CoV-2-infected persons who required hospital admission.…”
Section: Case Selection and Inclusion Criteriamentioning
confidence: 99%
“…10 It is managed through the Iran Ministry of Health and since the start of the COVID-19 pandemic has been a valuable and unique source of real-time data for recording the effects of SARS-CoV-2 infection on pregnant women and their babies. In addition to hospital births, IMaN records almost all births, both liveborn and stillborn, selected demographics, and maternal and neonatal health information electronically from throughout the country [10][11][12] To describe the Iranian national experience with COVID-19 among neonates, we conducted a retrospective analysis of the accumulated data in the IMaN for a 1-year period beginning at the start of the pandemic. This communication describes the epidemiological and clinical spectrum of COVID-19 from 4,015 neonates from throughout Iran who were suspected or confirmed as having SARS-CoV-2 infection following delivery to an infected mother and discusses current concepts of the pathophysiology of vertical infection.…”
mentioning
confidence: 99%